Determining the Selected Social Network of Employees of Shahroud University of Medical Sciences to Receive News of Covid-19 - Taherparvar , Nina; Sheibani , Hossein; Seidabadi , Arash; Talebi , Seyedeh Solmaz; Noyani , Amir (Shahroud Journal of Medical Sciences, 2023)
Background: Today, social networks play a very important role in communication between people. Many people use social networks as a source of information and a means of sending messages. This study aimed to determine the selected social network among the staff of Shahroud University of Medical Sciences.Methods: This cross-sectional study was conducted at Shahroud University of Medical Sciences in 2020. Different variables, such as demographic characteristics, amount of interest in each social network, hours of using the Internet, trustworthiness, being up-to-date, accessibility, number of visits to each network, effectiveness, and how information is shared, and also the relationship between these variables were examined. The significant level was set at 0.05.Results: A total of 109 (28.2%) women and 277 (71.8%) men participated in this study. The majority of the participants were aged 30-40 years (50%) and had a bachelor’s degree (55.2%). All the participants were members of at least one social network. The participants rated Telegram and then WhatsApp as the most frequently-visited, accessible, trusted, and up-to-date social networks.Conclusions: According to the findings of this study, Telegram and then WhatsApp is the social network of choice among the majority of the staff.Key Words: Social networking, COVID-19, News, Medical staff